2012
DOI: 10.1111/j.1750-3841.2012.02800.x
|View full text |Cite
|
Sign up to set email alerts
|

Bitter Taste Inhibiting Agents for Whey Protein Hydrolysate and Whey Protein Hydrolysate Beverages

Abstract: The bitter taste of whey protein hydrolysates (WPH) limits their use as ingredients. This study identified effective bitter taste inhibitors of WPH with different peptide composition and provides insights for effective bitter inhibitors for product applications with WPH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 32 publications
2
48
0
1
Order By: Relevance
“…Our results are in agreement with that mentioned by Leksrisompong et al, (2012) who found that the salts and nucleotides decreased bitter taste intensity of WPH. However, they also potentiated their own flavors or muted other desired flavors(vanilla or chocolate flavors), or sweet taste.…”
Section: Fig 2 Rp-hplc Pattern Of Hydrolyzed Product Of Mpc By Trypsupporting
confidence: 83%
“…Our results are in agreement with that mentioned by Leksrisompong et al, (2012) who found that the salts and nucleotides decreased bitter taste intensity of WPH. However, they also potentiated their own flavors or muted other desired flavors(vanilla or chocolate flavors), or sweet taste.…”
Section: Fig 2 Rp-hplc Pattern Of Hydrolyzed Product Of Mpc By Trypsupporting
confidence: 83%
“…Hydrolysates of whey protein have been widely studied for ACE-inhibitory activity (Abubakar, Saito, Kitazawa, Kawai, & Itoh, 1998;O'Loughlin et al, 2014;Pihlanto-Leppälä et al, 2000;Wang, Mao, Cheng, Xiong, & Ren, 2010;Wang et al, 2012) and have been reported to have bitter taste (Cheison et al, 2007;Leksrisompong, Gerard, Lopetcharat, & Drake, 2012;Leksrisompong, Miracle, & Drake, 2010). Therefore, whey protein was selected as the substrate for producing hydrolysates in the current study.…”
Section: Introductionmentioning
confidence: 99%
“…Enzymatic hydrolysis leads to break down of α-lactalbumin, β-lactoglobulin, serum albumin and β-casein, liberating the bitter peptides. Different inhibitors capable of masking the unpleasant taste of whey protein hydrolysate were studied (Leksrisompong et al 2012). Sucralose, fructose, sucrose, adenosine 5′ monophosphate (5'AMP), adenosine 5'monophosphate disodium, sodium acetate, monosodium glutamate, sodium gluconate and sodium chloride were found effective in concealing the bitterness.…”
Section: Quality Improvement/combination With Other Supplementmentioning
confidence: 99%